2012
DOI: 10.1038/ng.2371
|View full text |Cite
|
Sign up to set email alerts
|

The draft genome of a diploid cotton Gossypium raimondii

Abstract: Cotton is one of the most economically important crop plants worldwide. Its fiber, commonly known as cotton lint, is the principal natural source for the textile industry. Approximately 33 million ha (5% of the world's arable land) is used for cotton planting 1 , with an annual global market value of textile mills of approximately $630.6 billion in 2011 (MarketPublishers; see URLs). Apart from its economic value, cotton is also an excellent model system for studying polyploidization, cell elongation and cell w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
833
2
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 878 publications
(867 citation statements)
references
References 44 publications
25
833
2
7
Order By: Relevance
“…The assembled A subgenome (1,477 Mb) is nearly twice the size of the D subgenome (831 Mb), which is consistent with the genome size difference between G. arboreum 2 and G. raimondii 3,4 . At least 64.8% of the assembled genome are transposable elements (TEs), which was substantially higher than that in canola (>34.8%) 9 , but lower than in wheat (>76.6%) 6 .…”
Section: Comparative Genome Analysessupporting
confidence: 75%
See 1 more Smart Citation
“…The assembled A subgenome (1,477 Mb) is nearly twice the size of the D subgenome (831 Mb), which is consistent with the genome size difference between G. arboreum 2 and G. raimondii 3,4 . At least 64.8% of the assembled genome are transposable elements (TEs), which was substantially higher than that in canola (>34.8%) 9 , but lower than in wheat (>76.6%) 6 .…”
Section: Comparative Genome Analysessupporting
confidence: 75%
“…6a and 7). However, this colinearity was not obvious with either the A-progenitor genome (G. arboreum) 2 or another version of the D-progenitor genome (G. raimondii) 3 because of numerous mis-assemblies. For example, many scaffolds from several different pseudochromosomes were present in one pseudomolecule ( Supplementary Figs.…”
Section: Comparative Genome Analysesmentioning
confidence: 99%
“…A WGD has also previously been shown for the cotton lineage, after its speciation with cacao 25,26 . We investigated whether the WGDs associated with cotton and durian reflect the same event or represent two distinct evolutionary events, by resolving the ordering and dates of the WGDs alongside the durian-cotton divergence event.…”
Section: Comparative Phylogenomics Shows Durian Paleopolyploidymentioning
confidence: 60%
“…With the release of genomes sequences of two diploid cotton (A2, D5) and two allotetraploid cotton (AD1, AD2) (Phillips et al 2017;Li et al 2014;Paterson et al 2012;Wang et al 2012;Li et al 2015;Zhang et al 2015;Yuan et al 2015;Liu et al 2015) facilitates the survey of SWEETs in cotton. In this study, we identified the SWEETs in four cotton species by genome-wide analysis.…”
Section: Introductionmentioning
confidence: 99%